2009
DOI: 10.1021/jm900007a
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Constitutive Nitric Oxide Synthases in Complex with De Novo Designed Inhibitors

Abstract: New nitric oxide synthase (NOS) inhibitors were designed de novo with knowledge gathered from the studies on the nNOS-selective dipeptide inhibitors. Each of the new inhibitors consists of three fragments: an aminopyridine ring, a pyrrolidine, and a tail of various length and polarity. The in vitro inhibitory assays indicate good potency and isoform selectivity for some of the compounds. Crystal structures of these inhibitors bound to either wild type or mutant nNOS and eNOS have confirmed design expectations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Crystallographic analysis of new NOS inhibitors generated from the proposed fragment hopping method is described in detail elsewhere. 72 To briefly summarize, the structure of nNOS complexed with 4 (PDB accession 3B3N) was solved to 1.98 Å resolution with R/R free = 0.23/0.27, and the complex with 6 (PDB accession 3B3M) was solved to 1.95 Å with R/R free = 0.20/0.23). Only one of the two cis enantiomers, the (3′S,4′S)-isomer, was bound to the active site.…”
Section: Nos Inhibition Andmentioning
confidence: 99%
“…Crystallographic analysis of new NOS inhibitors generated from the proposed fragment hopping method is described in detail elsewhere. 72 To briefly summarize, the structure of nNOS complexed with 4 (PDB accession 3B3N) was solved to 1.98 Å resolution with R/R free = 0.23/0.27, and the complex with 6 (PDB accession 3B3M) was solved to 1.95 Å with R/R free = 0.20/0.23). Only one of the two cis enantiomers, the (3′S,4′S)-isomer, was bound to the active site.…”
Section: Nos Inhibition Andmentioning
confidence: 99%
“…These selectivities are comparable to those attained with nitroarginine-containing dipeptide derivatives 1-3 [28]. The crystallographic analysis shows that only the designed enantiomer was bound to the active site (PDB id, 3B3N) [77]. Figure 18.3a shows a superimposition of the binding conformations and the predicted bioactive conformation of 4 with nNOS, and Figure 18.3b shows a superimposition of the binding conformation of 2 (PDB id, 1P6I [71]) and 4 with nNOS.…”
Section: Fragment Hopping To Design Novel Inhibitors For Neuronal Nitmentioning
confidence: 57%
“…The aminopyridine end of the inhibitor should interact with the active site Glu while the pyrrolidine N atom should interact with Asp597 in nNOS but much more weakly with Asn368 in eNOS. The crystal structures showed that compounds like 8 bound to rat nNOS very close to what was predicted (PDB 3B3M and 3B3N) [41]. …”
Section: Second Generation Nnos Inhibitorsmentioning
confidence: 61%